Plagiarism in English academic writing: A comparison of Chinese university teachers' and students' understandings and stances. (February 2016) - Hu, Guangwei; Lei, Jun
Abstract: Research on plagiarism has largely left English-as-a-Foreign-Language (EFL) teachers out of the picture. This study set out to bridge the gap by comparing how 142 Chinese university EFL teachers and 270 undergraduate students viewed exemplars of unacknowledged copying and unattributed paraphrasing, two forms of intertextuality generally regarded as plagiarism in Anglo-American academia. More than half of the teacher participants had overseas academic experience. Quantitative and qualitative analyses found that the participants, though understanding plagiarism in English academic writing differently from Anglo-American academia, clearly disapproved of recognized cases of plagiarism. The analyses also revealed that greater knowledge of and harsher stances on both types of transgressive intertextuality were associated with wider exposure to and more experience in English academic writing. Furthermore, the participants had more similar understandings of unacknowledged copying than of unattributed paraphrasing and took harsher stances on the former. These findings highlight complex and nuanced understandings of plagiarism and point to the crucial role of academic socialization in shaping knowledge of and attitudes toward plagiarism.